Reimagining the Family - Payne, Robert (Peter Lang Ltd. International Academic Publishers, 2021)
Reimagining the Familyis the first book-length study of representations of lesbian mothering in French literature. Focusing on female-authored texts published between 1970 and 2013, the book explores how literature reflects, engages with and even anticipates the recent, highly charged debates on the rights of same-sex couples in France.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift; Electronic books; Französisch; Literatur; Lesbe; Mutter; Familie